1993
DOI: 10.1056/nejm199307153290302
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 in Lung Tissue from Patients with Pneumonitis after Bone Marrow Transplantation

Abstract: The concentrations of HHV-6 genome in lung tissue and their relation to changes in serologic titers support an association between HHV-6 infection and idiopathic pneumonitis in immunocompromised hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
154
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(158 citation statements)
references
References 29 publications
1
154
0
3
Order By: Relevance
“…Furthermore, HHV-6 has been shown to be capable of causing interstitial pneumonitis in this group of patients, 33 and in previous studies it has been significantly associated with the occurrence of GVHD and concurrent EBV. 34 However, only 1/5 findings of HHV-6 and 2/3 findings of EBV were considered to be the cause of pneumonia.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, HHV-6 has been shown to be capable of causing interstitial pneumonitis in this group of patients, 33 and in previous studies it has been significantly associated with the occurrence of GVHD and concurrent EBV. 34 However, only 1/5 findings of HHV-6 and 2/3 findings of EBV were considered to be the cause of pneumonia.…”
Section: Discussionsupporting
confidence: 50%
“…1 Furthermore, there are reports that HHV-6 infection is associated with an increased incidence of cytomegalovirus (CMV) and Epstein-Barr virus (EBV) infection 3 and the occurrence of graft-versus-host disease (GVHD). 4 To date, there are only three reports of HHV-6-associated encephalitis in patients after bone marrow transplantation in the literature and two proved to be fatal, demonstrating the potential morbidity and mortality of this infection. [5][6][7] As HHV-6 is susceptible to ganciclovir and foscarnet but less sensitive to acyclovir, 1 clinical disease caused by this virus is potentially treatable.…”
Section: Discussionmentioning
confidence: 99%
“…Human herpesvirus-6 (HHV-6) shares many biological characteristics with CMV, including viral protein products (ෂ67% homology), 1 antigenic reactivity, and in vitro growth characteristics. 2 Several studies have suggested that HHV-6 is associated with fever, skin rash, 3 graft-versus-host disease (GVHD), 4 interstitial pneumonitis, 5 encephalitis, 6,7 thrombotic microangiopathy (TMA), 8 and suppression of engraftment, 9 in bone marrow transplant recipients.…”
mentioning
confidence: 99%